Disaster Mitigation Training in Disaster Resistant Village in Tanjung Rejo Village Medan Sunggal Medan City - Ismayadi; Tanjung, Dudut (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2022)
The hydrometeorological flood disaster in Indonesia is influenced by climate change and inappropriate land conversion. Mitigation is generally carried out in the context of reducing losses due to the possibility of a disaster, be it loss of life and/or loss of property that will affect human life and activities. This Community Service activity was carried out in the Tanjung Rejo Village, which is located on Jalan Abadi Gang Balai Desa No. 13-B Medan District. The distance from the University of North Sumatra to Tanjung Rejo Village is 3.7 Km via Jl. Dr. Mansyur (about 11 minutes). Tanjung Rejo Sub-district is a sub-district located on lowland with an altitude of 24-37 meters above sea level and an average temperature of around 24Â°C to 32Â°C with an average Rainfall of 1,800-2,000 mm/year. In order to define an appropriate and accurate mitigation plan or strategy, it is necessary to carry out a risk assessment. Disaster mitigation activities should be routine and sustainable activities. This means that mitigation activities should have been carried out in the long period prior to disaster activities, which often come sooner than expected, and even have greater intensity than originally thought.